A case report on sinonasal undifferentiated carcinoma: a surgeon’s challenge or simply treatment challenges - Mariappen, Suraien; Lim, Walter Yung Chwen; Ng, Pui Foong; Maruthamuthu, Thevagi; Rozhan, 'Atikah (Sciencedomain International, 2025)
A 38-year-old Chinese gentleman presented to a private healthcare facility with a chief complaint of unilateral epistaxis, persisting for 2 months. An endoscopic examination revealed a polyp-like structure in the left nasal cavity, which bled upon contact. The patient underwent endoscopic sinus surgery and biopsy. Initial histopathological examination rendered as well differentiated squamous cell carcinoma. Post operatively, despite persistent nasal symptoms, the patient defaulted on treatment. Two months later, he presented to the emergency department with painless, progressive left eye swelling, accompanied by left eye vision loss, reduced hearing, and tinnitus for 1 week. Examination revealed proptosis of the left eye, firm and non tender swelling over the left maxillary region, and a fleshy mass occupying the entire left nostril. Imaging studies showed extensive disease involving the nasal cavity, paranasal sinuses, left orbit with intracranial extension, and bony erosions. Histopathological examination from a biopsy confirmed Sinonasal Undifferentiated Carcinoma (SNUC). The patient was staged as cT4bN0M0 and planned for chemotherapy but defaulted after 2 cycles due to intolerable side effects. He succumbed to locally advanced disease a month later. SNUC is a rare and highly aggressive malignant neoplasm originating from the epithelial lining of the paranasal sinuses and nasal cavity. Its aggressive nature often results in large and extensive tumors at the time of diagnosis, with a short duration of symptoms. While initial treatment involves surgical resection, complete tumor removal is often challenging due to complex anatomy. Aggressive multimodality treatment is recommended, although SNUC carries a high rate of local recurrence and increased morbidity and mortality.